STRATEGI STATION KEEPING SATELIT GEO (STUDI KASUS SES-7) - Fitri, Elisa
An ideal GEO satellite is a satellite that has orbital element eccentricity e=0, inclination i=0, semimajor axis a=42,164.26687 km and meaningless to measure the argument of perigee ???? the right ascension of ascending node ????. This function of satellite is as communication relay. Because of the Earth’s non-spherical perturbation and lunisolar perturbation, GEO orbital element will change with time. The change of orbital element cause satellite drifts from the nominal position to the East-West direction (longitude drift) and North-South direction (latitude or inclination drift). Orbital propagation is done for looking the drift direction of longitude and latitude. Orbital propagation shows propagation of orbit with time. In this final project, GEO satellite studied is SES-7, which located at 108.25° E. Orbital correction or maneuver is done in the direction of satellite drift, those are East-West maneuver and North-South maneuver. The software used to propagate orbit and maneuver is GMAT (General Mission Analysis Tool). In this simulation, three scenarios for East-West maneuver are considered, those are scenario 1 (14 days East-West and 28 days North-South maneuver), scenario 2 (14 days East-West and 14 days North-South maneuver), and scenario 3 (7 days East-West and 7 days North-South maneuver) which doing for 84 days. East-West maneuver is done with drift symmetry technique, meanwhile, North-South maneuver is done at right ascension of ascending node or right ascension of descending node. Scenario 1 has the smallest ????? requirement, followed by scenario 2 and 3, respectively. East-West maneuver should be performed before 84 days elapsed, because the satellite has reached the maximum of longitude deadband that caused by eccentricity change. But, North-South maneuver can be done longer. Therefore, I also did North-South maneuver with 0.05°, 0.08°, and 0.1° inclination limit for one year. As a result, the sequence of increasing maneuver velocity from the smallest is 0.1°, 0.008°, and 0.05° inclination limit.